HARMONI DI KAKI GUNUNG KUMBANG Ngasa, Komunitas Jalawastu dan Jejak Sunda di KabupatenBrebes - Wijartno Wijanarto (Department of Anthropology, 2018)
The diversity of Brebes Regency has been attributed through scattered heritage tracks both tangible and intangible. All of them frame the identity of the community in Brebes Regency. Among them are the Jalawastu community which is on the slopes of the Kumbang mountain. Jalawastu is a trace of Sundanese in Brebes Regency which still survives. They still maintain some traditions as one of the strengthening of identity as heirs of Sundanese culture. It feels synonymous with the appreciation of the Jalawastu community for their natural cosmology that lives at the foot of Mount Kumbang. In Ngasa's footsteps, the Jalawastu community explores their historical traces inherited through memory memories. Memory is the inheritance of traditional historiography stored in the folklore story. Most Jalawastu folklores include oral folklore. The substance of this study is based on cultural ecological relations with the physical environment that produces a number of cultural systems as well as symbols of social harmony